Terminal Parent Phosphanide and Phosphinidene Complexes of Zirconium(IV). Issue 26 (26th May 2017) - Stafford, Hannah; Rookes, Thomas M.; Wildman, Elizabeth P.; Balázs, Gábor; Wooles, Ashley J.; Scheer, Manfred; Liddle, Stephen T.
Abstract: The reaction of [Zr(Tren DMBS )(Cl)] [Zr1 ; Tren DMBS =N(CH2 CH2 NSiMe2 Bu t )3 ] with NaPH2 gave the terminal parent phosphanide complex [Zr(Tren DMBS )(PH2 )] [Zr2 ; Zr−P=2.690(2) Å]. Treatment ofZr2 with one equivalent of KCH2 C6 H5 and two equivalents of benzo‐15‐crown‐5 ether (B15C5) afforded an unprecedented example (outside of matrix isolation) of a structurally authenticated transition‐metal terminal parent phosphinidene complex [Zr(Tren DMBS )(PH)][K(B15C5)2 ] [Zr3 ; Zr=P=2.472(2) Å]. DFT calculations reveal a polarized‐covalent Zr=P double bond, with a Mayer bond order of 1.48, and together with IR spectroscopic data also suggest an agostic‐type Zr⋅⋅⋅HP interaction [∡ZrPH =66.7°] which is unexpectedly similar to that found in cryogenic, spectroscopically observed phosphinidene species. Surprisingly, computational data suggest that the Zr=P linkage is similarly polarized, and thus as covalent, as essentially isostructural U=P and Th=P analogues. Abstract : Together at last : Parent phosphanide and phosphinidene complexes of zirconium are prepared. The zirconium phosphinidene is the first example of a structurally authenticated transition‐metal terminal parent phosphinidene complex outside of matrix isolation experiments, and surprisingly, computational analysis of the bonding of the Zr=P double bond suggests this linkage is very similar to U=P and Th=P analogues.